Exploring Muslim Gen Z’s Financial Behavior: Roles of Islamic Literacy, Emotion Coping, and Self-Efficacy - Widyastuti, Emy; Mumtaz, Ni'am Al; Zahra, Karima (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The increasing complexity of modern life has made effective financial management an urgent challenge. This condition is particularly evident among Generation Z, who are vulnerable to consumptive behavior and instant lifestyle trends. This study explores and analyzes financial management behavior determinants through Islamic financial literacy and emotional coping involving financial self-efficacy as a moderating factor. The study was implemented in Salatiga using a quantitative approach. Questionnaires were distributed to obtain accurate primary data. The target population is Muslim Generation Z and, domiciled in Salatiga. The sample will be taken using a purposive sampling technique, and 100 respondents will be selected to obtain a representative sample. The findings through Structural Equation Modeling (SEM) PLS explain that Islamic financial literacy and emotional coping significantly contribute to improving good financial management in Muslim Gen Z. However, self-confidence depicted through financial self-efficacy is not enough to encourage a Muslim's financial literacy to manage their finances. Financial management for Muslim Gen Z will be influenced by their financial literacy, which is driven by self-efficacy. These findings contribute to the development of literature on financial behavior involving factors in the context of Islamic finance along with emotional factors, which are currently rarely studied.